ANALISIS POTENSI PAJAK DAERAH DALAM MENINGKATKAN PENDAPATAN ASLI DAERAH KABUPATEN ROKAN HULU - Nurhayati (Fakultas Ekonomi Universitas Pasir Pengaraian, 2015)
This study aimed to quantify and analyze the potential of local taxes to improve theoriginal income Rokan Hulu. The average contribution of each type of local taxes in 2008-2012 observations with an average contribution of 12.02%. The average growth of everykind of local taxes in 2008-2012 observations with an average growth of 19.30%.Identification or classification of types of local taxes Rokan Hulu potential based on thecriteria of growth and contribution criteria consists of: local tax is a tax that primarestaurants and street lighting tax. Local tax taxes mineral potential is not logan and rocks.Local tax is a tax that develops underground water and fees for acquisition of land andbuilding rights. Tax underdeveloped areas is hotel tax, entertainment tax and advertisementtax. Local tax elasticity calculations Rokan Hulu during the period 2008 to 2012 showed anincrease elasticity value and per capita income growth also increased. Increased growth ofper capita income elastic with increasing growth of local taxes. The period 2008-2009 theincrease in per capita income is less than 1% of 0.94%. In 2009-2010 the growth of incomeper capita amounted to 1.72%, also has the potential to increase the growth of local taxes,as well as in 2010-2011 the increase in per capita income growth of 2.92% is also thepotential to increase growth and local taxes in 2011-2012 increased revenue per capita of5.22% also has the potential to increase the growth of local taxes.